Miara konkurencyjności regionu zorientowana na przyszłość - Strahl, Danuta (Future-oriented measure of regional competitivenes, 2005)
The article proposes a construction of future-oriented measure of regional competitiveness. The article refers to some widely accepted factors of regional competitiveness and suggests five spheres of measuring capacities of a region. Those include human capital, lifestyle, innovation, financial resources, and finally availability and efficient use of information. Such a measure would be future-oriented thanks to, on one hand, the set of selected regional capacities that allow identification of the region’s development potential, and on the other - preferences for information related to current research period. The measure is constructed on the basis of formal comparative multivariate analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 23-33